Breast Cancer Stage Is Associated With Exceeding Target Price in the Oncology Care Model. Issue 11 (November 2021) - Thomas, Ryan B.; Maio, Vittorio; Chen, Anna; Park, Seojin; Waters, Dexter; Keith, Scott W.; Walsh, Karen; Handley, Nathan; Csik, Valerie P.
Abstract : PURPOSE: To explore mean difference between Oncology Care Model (OCM) total costs and target price among breast cancer episodes by stage under the Centers for Medicare and Medicaid Services OCM payment methodology. METHODS: Breast cancer episodes from OCM performance period 1-4 reconciliation reports (July 1, 2016-July 1, 2018) were linked with health record data from a large, academic medical center. Demographics, total cost of care (TCOC), and target price were measured by stage. Adjusted differences between TCOC and target price were compared across cancer stage using multivariable linear regression. RESULTS: A total of 539 episodes were evaluated from 252 unique patients with breast cancer, of which 235 (44%) were stage I, 124 (23%) stage II, 33 (6%) stage III, and 147 (27%) stage IV. About 37% of episodes exceeded target price. Mean differences from target price were –$1, 782, $2, 246, –$6, 032, and $11, 379 all in US dollars (USD) for stages I through IV, respectively. Stage IV episodes had highest mean TCOC ($44, 210 USD) and mean target price ($32, 831 USD) but also had higher rates of chemotherapy, inpatient admission, and novel therapy use. After adjusting for covariates, stage IV and ≥ 65-year-old patients had the highest mean difference from target price ($17, 175 USD; 95% CI, $12, 452 to $21, 898 USD). CONCLUSION: Breast cancer episodes in older women with distant metastases most frequently exceeded target price, suggesting that target price did not adequately account for complexity of metastatic cancers. A metastatic adjustment introduced in PP7 represents a promising advancement in the target price methodology and an impact evaluation will be needed.